Revalidasi Metodologi Zaid B Tsabit dalam Pemushafan Al-Qur’an - Fathurrofiq Fathurrofiq (Sekolah Tinggi Ilmu Al-Quran Dan Sains Al-Ishlah, 2020)
What Zaid b Tsabit did to collect the revelation of Quran, according to Muslim narratives was philologically perfect. At least, it is the most scrutinizing actever dealing with codifying scripture text. But to Western scholars (orientalists) view, it is not so. They find vague surrounding the Zaid b Tsabit works in the reign of either Abu Bakr or Uthman b Affan. The disputes on whether the Suhuf belong to Abu Bakr is official codex ot not, the Mushaf belong to Uthman was not soon widely accepted for example by Abdullah b Mas’ud the senior companion of the Prophet Muhammad in Kuffa, or the rising variants in reciting Quran were among the fertile lands for orientalists to criticize. Disputing Quran scientifically of course it is the challenge for Muslim to reaffirm his or her belief. So, it is open for whomever to criticize every aspect of Muslim life including their main theological source: Al-Qur’an. Responding the critics, thisresearch tries to revalidate philologically Zaid’s methodology. However, philology is scientific approach rooted from West tradition. In addition, to objectify, this research provides the comparasion of Zaid’s methodology to some philological experiences. The three examples of such experiences are philology belong to Alexandria school, philology of Bible, and philology of Nusantara. So, this research has two steps. Firstly, it explains the methodology belongs to Zaid its self philologically. Secondly in the same time, it compares to other philological experiences. By such explanation and comparison, this research try to reaffirm the very detailed and selective work of Zaid b Tsabit dealing with compelling the revelation of Qur’an.